The National Paedaitric Diabetes Register and its impact on healthcare - ROCHE, EDNA (My University, 2014)
In the field of management it has long been recognised that effective management of any given outcome requires knowledge and control of inputs to the system. This is also true in healthcare particularly in Type 1 diabetes (T1D), a common and severe chronic disease in childhood which is a huge health, social and economic burden1,2. In T1D the outcome, in terms of prevention of diabetes related complications, has been clearly shown to be related to resource dependent disease management3 and more recently the Hvidore Study group demonstrated better glycaemic control in those patients with more clinical contact4.
PUBLISHED
Keywords: Diabetes